2000
DOI: 10.1097/00019606-200006000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Novel Polymerase Chain Reaction Approach for Full-Coding p53 Mutation Detection in Microdissected Archival Tumors

Abstract: Evidence suggests that up to 25% of p53 mutations are outside of exons 5-8 and that insertions, deletions, and polymorphic sites in the p53 gene may play a significant role in the process of carcinogenesis. A novel polymerase chain reaction (PCR) approach for the analysis of the entire p53 coding and splice site regions from microdissected, formalin-fixed, paraffin-embedded tumor tissues has been developed which allows multiple genetic analyses to be performed from one primary amplification reaction. The metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…It has been reported that IRF-1 cooperate with the tumor suppressor p53-a cooperation necessary for some cells to undergo apoptosis. 31 Interestingly, both HN5 and A431 cell lines are known to carry mutations in the gene encoding p53, 32,33 suggesting that IRF-1 may be unable to induce apoptosis because of the lack of functional p53. A number of studies have reported IFN-associated genes or ''IFN signatures'' associated with human cancers.…”
Section: Egf Induces Irf-1 and Decrease Cell Viabilitymentioning
confidence: 99%
“…It has been reported that IRF-1 cooperate with the tumor suppressor p53-a cooperation necessary for some cells to undergo apoptosis. 31 Interestingly, both HN5 and A431 cell lines are known to carry mutations in the gene encoding p53, 32,33 suggesting that IRF-1 may be unable to induce apoptosis because of the lack of functional p53. A number of studies have reported IFN-associated genes or ''IFN signatures'' associated with human cancers.…”
Section: Egf Induces Irf-1 and Decrease Cell Viabilitymentioning
confidence: 99%
“…28,34 p53 mutations (exons 5 through 8) were detected by direct sequence analysis of PCR products. 34,35 Statistics. Statistical analysis was performed using SPSS.…”
mentioning
confidence: 99%
“…In comparison to the GenBank TP53 gene sequence used as reference (EM:U94788), two somatic intronic sequence variations were identified. This duplication has been identified in our laboratory in HN5 and A431 cell lines and in an ovarian cancer sample [46], but not in any of the gliomas analysed in this study. The intron 7 variation was found in only one Gen-Bank submission, in a sequence also derived from an astrocytoma (EM:AF136270).…”
Section: Discussionmentioning
confidence: 45%
“…TP53 mutation detection used a novel PCR methodology, which, by use of multiple simultaneous amplification of all TP53 amplicons within a single first round reaction, reduces markedly the amount of clinical material required for full analysis [46]. More extensive sequence data, including some intronic sequence, is obtained using this primer set compared with most other TP53 methodologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation